2010
DOI: 10.1590/s0103-73312010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Trabalho, abuso de drogas e os aparelhos ideológicos de estado: um estudo com alunos do ensino médio e fundamental

Abstract: A pesquisa se baseia em trabalho de prevenção de dependência entre estudantes de 23 municípios de quatro regiões brasileiras. Foram analisados 68.210 questionários referentes a Região Norte (29.386 questionários / 7 cidades), Região Nordeste (17.971 questionários / 3 cidades), Região Sudeste (4.197 questionários / 4 cidades) e Região Sul (16.656 questionários / 9 cidades). Os questionários continham 25 perguntas, das quais oito foram estudadas. Encontraram-se respostas aproximadas em todas as regiões brasileir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…With regard to the lifetime use of other drugs, the present study identified a prevalence of 5.0%. This result is similar to that of a study assessing 23 cities of four Brazilian regions that found an overall prevalence of 4.0% and of 6.0% for southern Brazil 35 . However, this percentage was different from that of the study conducted by Malta et al 15 , who found that the reported lifetime use of illicit drugs among students was 7.3%, and from CEBRID data, which found a prevalence of lifetime use of drugs of up to 33.0% 11 .…”
Section: Discussionsupporting
confidence: 90%
“…With regard to the lifetime use of other drugs, the present study identified a prevalence of 5.0%. This result is similar to that of a study assessing 23 cities of four Brazilian regions that found an overall prevalence of 4.0% and of 6.0% for southern Brazil 35 . However, this percentage was different from that of the study conducted by Malta et al 15 , who found that the reported lifetime use of illicit drugs among students was 7.3%, and from CEBRID data, which found a prevalence of lifetime use of drugs of up to 33.0% 11 .…”
Section: Discussionsupporting
confidence: 90%
“…There are many schools that continue to not pay attention to the individual differences of students, thus generating great difficulties, especially for those most socially and economically vulnerable. However, we understand that, from multidisciplinary and interdisciplinary programs of prevention of the use of alcohol and drugs, schools can respond to different individual demands in the field of prevention and, thus, play its effective role contributing to the promotion of health, which is an agreement among researchers (26) .…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Laranjeira (2014), 40% dos dependentes de bebidas alcoólicas são do gênero feminino, o que representa três vezes mais que na última década, indicando que a cada dez mulheres que consomem esse produto, cinco são dependentes do álcool. Câmara (2010) ressalta que nos anos de 1980, as meninas começavam a ingerir bebidas adocicadas e de baixo teor alcoólico aos 17 anos, hoje iniciam aos 13 anos e com cerveja e destilados.…”
Section: Introductionunclassified